Perancangan Sistem Informasi Otorisasi Aktifitas Ruang Server - Agni Isador Harsapranata (Prosiding Seminar Nasional Teknoka, 2020)
With the rapid development of computer technology today, it encourages authors to conduct research in the field of information systems. Where in the information system that the author does is with a problem that occurs in the writer monitoring all server room activities. In this case the author has had difficulty recording all activities carried out in the server room. Because if it does not record all activities carried out in the server room, it will result in server work that cannot be controlled and non-standard configurations carried out by the administrator. With this information system, it can monitor what has been done, and which servers need more attention by the administrator. In making this information system the author uses a web-based open source application, where the programming language used is Php, the web server used is Apache and utilizes the Mysql database. By utilizing a web-based open source application, this application can be installed on any server, and can be accessed using various operating systems includingusing a smartphone.